2017
DOI: 10.1016/j.jand.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

What’s Being Served for Dinner? An Exploratory Investigation of the Associations between the Healthfulness of Family Meals and Child Dietary Intake

Abstract: Background Little is known about the healthfulness of foods offered at family meals or the relationship between the food’s healthfulness and child overall dietary intake. Objective This exploratory study uses a newly-developed Healthfulness of Meal (HOM) index to examine the association between the healthfulness of foods served at family dinners and child dietary intake. Design Direct observational, cross-sectional study. Participants/setting Primarily low-income, minority families (n=120) video-recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
(37 reference statements)
1
49
0
Order By: Relevance
“…Component scores are summed, and the maximum total score is 9, indicating a higher quality meal. A comprehensive description of the HOM index development and coding can be found elsewhere (Trofholz et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Component scores are summed, and the maximum total score is 9, indicating a higher quality meal. A comprehensive description of the HOM index development and coding can be found elsewhere (Trofholz et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Dietary recalls were conducted with parents of younger children (6–8 year olds); recalls with older children (9–12 year olds) were conducted with child, although clarification by a parent was permitted. Dietary recalls were collected using Nutrition Data System for Research (NDSR) software version 2012, developed by the Nutrition Coordinating Center at the University of Minnesota; a detailed review was conducted by staff dietitians on 100% of recalls (Trofholz et al, 2015). Using data from these recalls, a Healthy Eating Index-2010 (HEI) score was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In considering strategies to raise fruit and vegetable consumption, there is some evidence that the foods present at family meals are associated with children and adolescent's overall dietary intake of those same foods (Arcan et al, 2007; Boutelle, Fulkerson, Neumark-Sztainer, Story, & French, 2007; Trofholz et al, 2015). For example, a longitudinal study found that adolescents who were served vegetables and milk at family dinners were more likely to consume those foods at a 5-year follow-up (Arcan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a longitudinal study found that adolescents who were served vegetables and milk at family dinners were more likely to consume those foods at a 5-year follow-up (Arcan et al, 2007). Another cross-sectional study found that serving vegetables, dairy, and empty calories (e.g., sugar-sweetened beverages) at dinner was significantly associated with 6-12 year olds’ overall intake of those same foods (Trofholz et al, 2015). We are not aware of any published research examining the relationship between serving fruit at family meals and children or adolescent's intake of fruit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation